2021
DOI: 10.1002/aelm.202100333
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Dielectric Al2O3/β‐Ga2O3 Interfaces Grown Using Metal–Organic Chemical Vapor Deposition

Abstract: as the gate dielectric for device applications. For transistor applications, a gate dielectric should exhibit low leakage currents, have low interface trap densities to achieve a controllable threshold voltage (V T ), and should also have a higher breakdown field compared to the underlying semiconductor. Many insulators such as SiO 2 , [3][4][5][6] Al 2 O 3 , [7,8] SiN, [9] and HfO 2 [9,10] have been studied as a gate oxide material and passivation layers for gallium oxide devices. Extreme permittivity materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…To determine density of all the all the interface states and their energy dependence deep ultra-violet (DUV) assisted CV measurements were performed. The detailed description of the methodology is provided elsewhere (31). The MOSCAPs were first taken from D-A, and kept at accumulation for 10 minutes to fill all the traps.…”
Section: In-situ Dielectricmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine density of all the all the interface states and their energy dependence deep ultra-violet (DUV) assisted CV measurements were performed. The detailed description of the methodology is provided elsewhere (31). The MOSCAPs were first taken from D-A, and kept at accumulation for 10 minutes to fill all the traps.…”
Section: In-situ Dielectricmentioning
confidence: 99%
“…Various reports exist on the study of dielectric on β-Ga 2 O 3 to improve the interface quality and breakdown field (24)(25)(26)(27)(28)(29)(30). In this paper we discuss the improvement of interface quality between the dielectric and β-Ga 2 O 3 using in-situ MOCVD-grown Al 2 O 3 , where Al 2 O 3 is grown on βGa 2 O 3 in the same reactor without breaking the vacuum (31). We also discuss the design of an optimum β-Ga 2 O 3 schottky barrier diode (SBD) (32) using p-type III-nitride guard rings for enhanced breakdown to circumvent the absence of p-type doping (33).…”
Section: Introductionmentioning
confidence: 99%
“…Improved growth, material quality and fabrication techniques lead to rapidly increasing β-Ga 2 O 3 power device performance with breakdown voltages, V BR , up to 8.32 kV, breakdown fields up to 6.45 MV cm −1 , and high power figure of merit up to 13.2 GW cm −2 [7][8][9][10][11][12][13][14][15][16][17]. Field-effect transistors (FETs) designed for radio frequency performance have also been fabricated [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, one strategy to scaling Si CMOS technology under limited static power consumption is to employ materials with a high dielectric constant (high-κ) as the gate dielectric layer, which allows the EOT and supply voltage (V dd ) to be reduced at the single-transistor level. Most of the studies reported substituting SiO 2 with high-κ materials, such as HfO 2 [8][9][10], ZrO 2 [11][12][13], Al 2 O 3 [14][15][16] as a gate oxide. However, in current Si-based device development, high-κ materials have a lattice mismatch with Si, making high-κ materials difficult to grow on the surface of Si with good quality.…”
Section: Introductionmentioning
confidence: 99%